2021
DOI: 10.3390/brainsci11020173
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Magnetic Resonance Imaging in Adult Post-Ganglionic Brachial Plexus Traumatic Injuries: A Systematic Review and Meta-Analysis

Abstract: Background: Traumatic brachial plexus injuries are rare but serious consequences of major traumas. Pre-ganglionic lesions are considered irreparable, while post-ganglionic injuries can be potentially treated if an early diagnosis is available. Pre-surgical diagnosis is important to distinguish low-grade from high-grade lesions and to identify their location. The aim of the review is to evaluate the diagnostic accuracy of magnetic resonance imaging (MRI) in the identification of adult post-ganglionic lesions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
10
0
4
Order By: Relevance
“…Considering this small variability, a specific analysis of the diagnostic accuracy of acute ATFL lesions with varying MRI field strength was not carried out. Furthermore, it is reported that there are no significant differences in the diagnostic performance of MRI using a 3 T magnet rather than a 1.5 T one; significant advantages can only be obtained with a field strength of 7 T, which provides better depiction of ankle anatomy, fluid depositions, and cartilage defects [54][55][56][57]. All the selected studies except for Wei Tan et al described the MRI protocols used, which showed substantial homogeneity: T2-weighted Turbo Spin Echo acquired in the axial plane was employed as the main sequence for a better visualization of the ATFL, using a section thickness of 3-4 mm with an interslice gap of 10%, with the only exception being Verhaven et al, in which a 3D-FSP sequence with a section thickness of 1 mm was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this small variability, a specific analysis of the diagnostic accuracy of acute ATFL lesions with varying MRI field strength was not carried out. Furthermore, it is reported that there are no significant differences in the diagnostic performance of MRI using a 3 T magnet rather than a 1.5 T one; significant advantages can only be obtained with a field strength of 7 T, which provides better depiction of ankle anatomy, fluid depositions, and cartilage defects [54][55][56][57]. All the selected studies except for Wei Tan et al described the MRI protocols used, which showed substantial homogeneity: T2-weighted Turbo Spin Echo acquired in the axial plane was employed as the main sequence for a better visualization of the ATFL, using a section thickness of 3-4 mm with an interslice gap of 10%, with the only exception being Verhaven et al, in which a 3D-FSP sequence with a section thickness of 1 mm was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that imaging and electrodiagnostic methods still lack precision in diagnosing nerve root conditions. [11][12][13][14] To date, the gold standard for the diagnosis of brachial plexus injuries is surgical exploration. 12,13 Radiography: after ruling out associated injuries, request a chest radiograph to assess the elevation of the hemidiaphragm resulting from potential damage to the phrenic nerve and detect any rib fractures, which can influence the choice of nerves for transfer.…”
Section: Additional Studiesmentioning
confidence: 99%
“…Según la evidencia actual, los métodos de imágenes y electrodiagnósticos todavía carecen de precisión para diagnosticar el estado de las raíces nerviosas. [11][12][13][14] Hasta el momento, el estándar de oro para el diagnóstico de las lesiones del plexo braquial es la exploración quirúrgica. 12,13 Radiografías: luego de descartar lesiones asociadas, se debe solicitar una radiografía de tórax para evaluar el ascenso del hemidiafragma por una posible lesión del nervio frénico.…”
Section: Estudios Adicionalesunclassified
See 1 more Smart Citation
“…Several diagnostic tools for BP injury are currently available, with MRI considered one of the best for the assessment of both peripheral nerve pathology and adjacent soft tissue and musculature [ 4 ]. In a review study, Leigheb et al [ 5 ] provided evidence to further support the use of MRI for pre-surgical diagnosis of BP injury. Through a meta-analysis on a set of recent studies combining MRI with intraoperative findings, Leigheb and colleagues evaluated the diagnostic accuracy of MRI for post-ganglionic lesions.…”
mentioning
confidence: 99%